Do We Really Not Know What Toulmin’s Analytic Arguments Are? - Kollárik, Tomáš (Informal Logic)

(untitled) (Informal Logic, 2023)
The aim of this paper is to challenge the idea that Toulmin’s main focus in The Uses of Argument is to critique formal deductive logic. I first try to challenge the argument that, on the basis of what Toulmin says about analytic arguments, it is impossible to determine exactly what they are. I will then attempt to determine the basic contours of analytic arguments. Finally, I will conclude that the concept of an analytic argument involves epistemological assumptions to which formal logicians are in no way committed by the nature of their discipline.